Analisis Nilai-Nilai Pendidikan Karakter Dalam Film Fetih 1453 Dan Implementasinya Dalam Pendidikan Islam Siswa-Siswi Era Modern - Mujtahid; Ali Hasan Assidiqi; Dini Sadiyah; M Zam-Zam Afkar (Jurnal Ilmu Agama Indonesia, 2025)
Film is one of the best media for educational learning. This is because films contain specific values, which can influence viewers, especially in shaping their characters. However, it is important to understand that not all films have a positive side; some also have negative aspects. With this understanding, it is crucial for researchers to examine the character education values ​​contained in films, particularly Fetih 1453, known as a historical film about the Islamic world and widely enjoyed by the public. The purpose of this study is to understand the character education values ​​contained in the film and to determine their implementation in modern student education, so that this film can serve as an example for students in their daily lives. This study used library research, focusing on the character education values ​​in the film. This research was conducted over approximately three months. The analysis used was descriptive analysis. The results showed that: 1) There are ten character education values ​​contained in the film Fetih 1453: religious, tolerance, discipline, hard work, creative thinking, love of the homeland, respect, friendship and communication, love of peace, and responsibility. 2) The implementation of this film is mandatory viewing and teaching by teachers. In this modern era, students must be provided with appropriate instruction, with an easy-to-understand introduction, and also be taught through daily life practices to emulate the film. This will help children understand the material well, even in a modern context.